PERAN PENDIDIKAN RESOLUSI KONFLIK DALAM MENCEGAH PERUNDUNGAN (BULLYING) DI LINGKUNGAN SEKOLAH - Deki Wibowo; Manggalastawa; Moh. Aris Prasetiyanto; Yoga Awalludin Nugraha (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Abstract: This study aims to analyze the role of conflict resolution education in preventing bullying behavior in elementary school settings. The research employed a qualitative approach using the library research method. Data were collected from a range of scholarly sources, including books, national and international journal articles, and other relevant academic literature. The data were analyzed using content analysis through the stages of data reduction, data presentation, interpretation, and conclusion drawing. The findings reveal that conflict resolution education plays a crucial role in enhancing students' abilities to regulate their emotions, develop empathy, appreciate diversity, and resolve conflicts peacefully without resorting to violence. The implementation of conflict resolution education through its integration into classroom instruction, the strengthening of character education, conflict mediation practices, and collaborative partnerships between schools and parents has proven effective in fostering a safe, supportive, and inclusive school climate, thereby reducing the incidence of bullying. Therefore, conflict resolution education represents an effective preventive strategy for cultivating a culture of peace in elementary schools and promoting a safe and positive learning environment for all students.